SOCS, Inflammation, and Autoimmunity - Yoshimura, Akihiko; Suzuki, Mayu; Sakaguchi, Ryota; Hanada, Toshikatsu; Yasukawa, Hideo (Frontiers in Immunology, 2012)
Cytokines play essential roles in innate and adaptive immunity. However, excess cytokines or dysregulation of cytokine signaling can cause a variety of diseases, including allergies, autoimmune diseases, inflammation, and cancer. Most cytokines utilize the so-called Janus kinase-signal transducers and activators of transcription (JAK-STAT) pathway. This pathway is negatively regulated by various mechanisms including suppressors of cytokine signaling (SOCS) proteins. SOCS proteins bind to JAK or cytokine receptors, thereby suppressing further signaling events. Especially, SOCS1 and SOCS3 are strong inhibitors of JAK, because these two contain kinase inhibitory region (KIR) at the N-terminus. Studies using conditional knockout mice have shown that SOCS proteins are key physiological as well as pathological regulators of immune homeostasis. Recent studies have also demonstrated that SOCS1 and SOCS3 are important regulators of helper T cell differentiation and functions.